Negotiating in Silence: Experiences with Parental Leave in Academia - Weststar, Johanna (Relations industrielles / Industrial Relations, 2012)
This paper presents a case study of pregnancy/parental leave arrangements among faculty members at a mid-sized Canadian University from 2000-2010. The data show that leave arrangements were very inconsistent across faculties, across and within departments, and even for individual faculty members who had taken more than one leave. The majority of problematic cases were instances where a faculty member began or ended a leave in the middle of an academic term. Without specific language in their collective agreement, these faculty members often negotiated circumstances that carried individual penalties for duties that were unassigned in light of the leave. This research has implications for unions who must be particularly vigilant and active in professional environments where individual negotiation takes place and union consciousness is lower. It also emphasizes the burden placed on parents when the bearing and rearing of children is framed as an individual right rather than an issue of social reproduction. The paper uses data from a sample of collective agreements across Canadian universities to make recommendations to clarify the procedures for pregnancy and parental leave.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Colleges & universities; Labor Unions; Labor relations; Maternity & paternity leaves; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; University faculty

Give Me the Room to Learn: Associations between Job Control and Work-Related Learning - Weststar, Johanna (Just Labour: A Canadian Journal of Work and Society, 2007)
Societal rhetoric claims that the intellectual capital of workplaces must be leveraged if Canada is to compete in the "knowledge economy". To achieve this, however, employers must create work environments that are favorable to workers and conducive to learning. This paper uses a sample of 5800 Canadian workers from the Work and Lifelong Learning Survey and twenty interviews with Information Technology workers from the Education-Job Requirement Matching Project to focus on the relationship between worker control and learning engagement. The data show that increased levels of social and technical control are associated with increased worker engagement in formal courses, informal education (mentoring) and non-taught learning. This research has implications for job design that includes real and meaningful opportunities for worker input and agency into their own tasks and broader organizational decision-making. These results provide important information for future research regarding the inclusion and conceptualization of learning and job control constructs.

Research Handbook of Employment Relations in Sport - Weststar, Johanna (Relations industrielles / Industrial Relations, 2019)
The article reviews the book, "Research Handbook of Employment Relations in Sport," edited by Michael Barry, James Skinner and Terry Engelberg.

Comment jouer la régulation dans l’industrie du jeu vidéo? - Legault, Marie-Josée; Weststar, Johanna (Relations industrielles / Industrial Relations, 2014)
Cet article étudie les choix des concepteurs de jeux vidéo en matière de représentation de leurs intérêts à la lumière de la théorie de la mobilisation de Kelly (1998), cela dans le but de mesurer leur disposition à l’action collective. Ces travailleurs illustrent bien le cas des travailleurs du savoir dans des productions organisées par projets. Si le modèle de Kelly permet en principe d’asseoir des projections concernant la syndicalisation d’un secteur, tel n’est pas le cas ici. Notre étude nous amène plutôt à mesurer l’ampleur de la transformation du marché de l’emploi depuis l’élaboration du modèle et la distance qui sépare les besoins des travailleurs du savoir, d’une part, et les options que leur propose l’action syndicale traditionnelle telle que présentée par le modèle de Kelly, d’autre part.Ce groupe de travailleurs remplit deux conditions propices à l’action collective : il a identifié des problèmes communs dans les conditions de travail de l’industrie et il en attribue généralement la responsabilité à l’employeur.Cependant, trois conditions essentielles l’empêchent de s’unir en une coalition. D’abord, il est partagé entre une définition de son intérêt en termes collectifs et individuels; ensuite , il est aussi partagé quant à la conviction que la situation insatisfaisante est illégitime. Enfin, et surtout, lorsque les travailleurs analysent les coûts et les bénéfices de l’action collective, le projet de syndicalisation via le régime général d’accréditation fondé sur l’entreprise-employeur leur pose plusieurs problèmes concrets. Les concepteurs de jeux pratiquent une forme d’action collective qui contourne les contraintes que pose notre régime juridique actuel de rapports collectifs de travail. Or, la théorie de la mobilisation de Kelly assimile action collective et action syndicale traditionnelle, ce qui mérite d’être reconsidéré.
Keywords: Diseñadores de juegos de video; acción colectiva; action collective; collective action; concepteurs de jeux vidéo; knowledge workers; organisation par projets; organización por proyectos; project-based organisations; sindicalización; syndicalisation; trabajadores del saber; travailleurs du savoir; unionisation; video game developers

Union Education, Union Leadership and Union Renewal: The Role of PEL - Weststar, Johanna (Paths to Union Renewal: Canadian Experiences, 2006)
[E]xamines the Paid Education leave (PEL) program, a negotiated employer-funded worker education program administered by the Canadian Auto Workers. The primary purpose of the study is to evaluate the ability of the PEL to develop membership knowledge, activism and leadership to facilitate union renewal. [The author's] paper, based on survey research and interviews, maintains that the PEL program does contribute to leadership development and to the union renewal process by serving to alter the perceptions and attitudes of its participants. –Editors' introduction
https://www.researchgate.net/publication/334539302_Chapter_18_Union_Education_Union_Leadership_and_Union_Renewal_The_Role_of_PEL https://utorontopress.com/9781551930589/paths-to-union-renewal/
Keywords: Canadian Auto Workers (CAW); Community unionism; Labor Unions; Labor movement; Organizational change; Paid Education Leave (PEL)

Symposium - Promising Practices in Scholar-Union Collaboration: Lessons for Building Effective Research Partnerships - Armstrong, Pat; Bittman, Kevin; Hurley, Michael; Stanford, Jim; Tucker, Sean; Vela, Jakin; Weststar, Johanna; Wilson, Fred (Relations industrielles / Industrial Relations, 2025)
This symposium considers the prospects for research collaboration between industrial relations scholars and trade unions, as well as its challenges. First, in remarks presented in the 2025 H.D. Woods Lecture at the Canadian Industrial Relations Association / Association canadienne des relations industrielles conference, Jim Stanford reviews the mutual benefits for both scholars and trade unionists from successful research partnerships and proposes strategies for building more respectful and trusting relationships between them. The symposium then presents three case studies of lasting, productive research partnerships, each described by a matched pairing of a scholar with a union representative. Lessons are drawn for future research collaborations.

Control and Insecurity in Australian and Canadian Universities during the COVID-19 Pandemic - Peetz, David; O’Brady, Sean; Weststar, Johanna; Coles, Amanda; Baird, Marian; Cooper, Rae; Charlesworth, Sara; Pyman, Amanda; Ressia, Susan; Strachan, Glenda; Troup, Carolyn (Relations industrielles / Industrial Relations, 2022)
We studied 14 universities across Canada and Australia to examine how the COVID-19 crisis, mediated through management strategies and conflict over financial control in higher education, influenced workers’ job security and affective outcomes like stress and happiness. The countries differed in their institutional frameworks, their union density, their embeddedness in neoliberalism and their negotiation patterns. Management strategies also differed between universities. Employee outcomes were influenced by differences in union involvement. Labour cost reductions negotiated with unions could improve financial outcomes, but, even in a crisis, management might not be willing to forego absolute control over finance, and it was not the depth of the crisis that shaped management decisions.
Keywords: Analyse comparative; Australia; Australie; COVID-19; Canada; Contrôle; Covid-19; Stratégies de gestion; Syndicat; Travailleurs universitaires; comparative analysis; control; contrôle financier; financial control; management strategies; negotiation pattern; négociation collective; union; university workers